Dyeing assessment and antimicrobial activity of tetra azo acid dyes derived from 4,4’-(propane-2,2-diyl)bis(2-methyl-4,1phenylene) bis(3-aminobenzenesulfonate) - Patel, Snehal N.; Patel, Navin B. (IJRDO-Journal of Applied Science, 2016)
4,4’-(Propane-2,2-diyl)bis(2-methyl-4,1-phenylene)bis(3-aminobenzenesulfonate) was synthesized by reduction of condense product of Bisphenol C and m-nitrobenzenesulfonyl chloride. The compound was used as a bifunctional middle component in the preparation of tetra azo acid dyes. This di amino compound was tetra azotized and coupled with naphthalene based acid coupling component to give various tetra azo acid dyes. The obtained dyes were characterized by spectroscopic technique (UV-vis., IR, NMR) and the dyeing assessment of all dyes was evaluated on wool, silk and nylon fabrics. These dyes gave brown, violet, yellow, orange and pink shades on each fibers with good to very good fastness properties. The percentage dye bath exhaustion, fixation and biological activity have also been studied.